Market Disequilibria and Inflation in Uzbekistan, 1994-2000 - Ranaweera, Thilak (World Bank, Washington, DC, 2014)
The author develops, and applies a macroeconomic framework to ascertain the influence of domestic disequilibria, and external shocks on inflation dynamics in Uzbekistan. Using quarterly data for the period 1994:01 to 2000:03, he estimates several "long-run" relationships for the goods, money, and foreign exchange markets of Uzbekistan, which are characterized by multiple exchange rates, import restrictions, and other domestic administrative controls. The empirical estimates, which use error correction mechanisms for different markets, show that domestic monetary, and output developments, and changes in the official exchange rate, compared with the parallel market rate, have had a significant influence on the short-run behavior of the foreign exchange market in Uzbekistan. Furthermore, disequilibria in the product, and money markets are the major forces driving short-run inflation dynamics in Uzbekistan. It should be noted that the study has been constrained by both the quantity, and the quality of quarterly data available for the Uzbekistan economy.